A systematic review and meta-analysis of the efficacy and adverse events of azacitidine-plus-lenalidomide treatment for patients with acute myeloid leukemia, myelodysplastic syndromes and chronic myelomonocytic leukemia1 - Chutima Kunacheewa (2020)
© 2019, © 2019 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group. Objectives: The addition of lenalidomide (LEN) to azacitidine (AZA) may further improve the outcomes of acute myeloid leukemia (AML) patients as well as patients with high-risk myelodysplastic syndrome (MDS) and chronic myelomonocytic leukemia (CMML) patients although the evidence for this combination treatment is still relatively limited. This meta-analysis aimed to evaluate efficacy and adverse effects of AZA plus LEN for the treatment of patients with high-risk MDS, AML or CMML. Methods: The current study systematically identified all cohort studies of patients with AML and/or MDS and/or CMML who received AZA in combination with LEN that reported the overall complete remission (CR) rate and/or overall response rate (ORR). A DerSimonian–d random–effects model with double arcsine transformation was used for the pooled rates and 95% confidence interval (CI) of the all outcomes. Results: A total of 10 studies with 406 patients were identified and included into the meta-analysis. The pooled CR rate after the treatment with AZA-plus-LEN regimen was 33.0% (95% CI, 27.7%–38.7%, I2 = 18%) while the pooled ORR was 49.9% (95% CI, 38.4%–61.5%, I2 = 72%). Nonetheless, adverse events including grade 3–4 neutrophil toxicity events, platelet toxicity events and febrile neutropenia were common with AZA-plus-LEN regimen. Conclusions: The current study may serve as a preliminary data to suggest that the addition of LEN may offer incremental benefit to patients with high-risk MDS, AML and CMML. However, randomized-controlled studies that directly compare the efficacy and adverse events of AZA-plus-LEN regimen versus AZA monotherapy are still needed.